UV-VIS methodology for the quantification of vegetable oil in adulterated olive oil (Research, Society and Development, 2021)
Olive oil is a high-value product aggregated the obtained simply by pressing the olives. Known for being a functional and preventive food for several diseases such as cancer, coronary heart disease, and lowering of bad cholesterol; its adulteration by the addition of vegetable oil of less commercial value becomes a practice in the industry. To facilitate the verification of adulteration, methods such as UV-Vis spectroscopy were used to quantify the vegetable oil present in virgin olive oil. This study aimed to understand the UV-Vis technique in a previous reading in the evaluation and investigation of adulteration in extra virgin olive oils available on the market through quantitative research. F pray laboratory samples tampered with 4 types of vegetable oil for evaluation of the reading spectrum responses. Calibration curves have been traces of and not there was a difference between the results of the oil were obtained from 0 to 70% substitution of olive oil by vegetable oil. Also, compound oils were analyzed to verify that the labeled percentage was being respected, obtaining results of up to 96% soy oil in a product that should contain a maximum of 88%. Therefore, it was possible to verify that the 456 nm region can be used to check adulterations with efficiency and agility and that UV-Vis spectroscopy can be considered a fast and low-cost method for previous analyzes.